Measurements of triple-differential cross sections for inclusive isolated-photon plus jet events in pp collisions at root s=8 TeV - Sirunyan, A. M.; Tumasyan, A. R.; Adam, Wolfgang; Ambrogi, Federico; Asilar, Ece; Md. Ali, Mohd. Adli (Springer Nature, 2019)
Measurements are presented of the tripledifferential cross section for inclusive isolated-photon+jet events in pp collisions at √s = 8 TeV as a function of photon transverse momentum (pγ T), photon pseudorapidity (ηγ), and jet pseudorapidity (ηjet). The data correspond to an integrated luminosity of 19.7 fb−1 that probe a broad range of the available phase space, for |ηγ| < 1.44 and 1.57 < |ηγ| < 2.50, |ηjet| < 2.5, 40 < pγ T < 1000 GeV, and jet transverse momentum, p jet T , > 25 GeV. The measurements are compared to next-to-leading order perturbative quantum chromodynamics calculations, which reproduce the data within uncertainties.